2014
DOI: 10.1530/joe-13-0592
|View full text |Cite
|
Sign up to set email alerts
|

PCSK6 regulated by LH inhibits the apoptosis of human granulosa cells via activin A and TGFβ2

Abstract: Mammalian proprotein convertases (PCs) play an important role in folliculogenesis, as they proteolytically activate a variety of substrates such as the transforming growth factor beta (TGFb) superfamily. PC subtilism/kexin 6 (PCSK6) is a member of the PC family and is ubiquitously expressed and implicated in many physiological and pathological processes. However, in human granulosa cells, the expression of the PC family members, their hormonal regulation, and the function of PCs are not clear. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…3). Sertoli and granulosa cells express enzymes that cleave proAMH, with the levels of the enzymes and/or their regulators varying during testicular (Nachtigal & Ingraham 1996, Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007) and ovarian (Bae et al 2008) development, the seminiferous cycle (Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007, the ovarian cycle (Bae et al 2008, Wang et al 2014, the stage of ovarian follicular development (Ohnishi et al 2005, Bae et al 2008, Antenos et al 2011) and during pregnancy (Kwok et al 2013). However, the AMH in ovine follicular fluid is predominantly proAMH with little AMH N,C (Campbell et al 2012), suggesting that AMH can be synthesised and released with little or no prior cleavage.…”
Section: Gonadal Cleavage Of Proamhmentioning
confidence: 99%
“…3). Sertoli and granulosa cells express enzymes that cleave proAMH, with the levels of the enzymes and/or their regulators varying during testicular (Nachtigal & Ingraham 1996, Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007) and ovarian (Bae et al 2008) development, the seminiferous cycle (Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007, the ovarian cycle (Bae et al 2008, Wang et al 2014, the stage of ovarian follicular development (Ohnishi et al 2005, Bae et al 2008, Antenos et al 2011) and during pregnancy (Kwok et al 2013). However, the AMH in ovine follicular fluid is predominantly proAMH with little AMH N,C (Campbell et al 2012), suggesting that AMH can be synthesised and released with little or no prior cleavage.…”
Section: Gonadal Cleavage Of Proamhmentioning
confidence: 99%
“… 19 , 20 PACE4 has the potential to participate in various cellular functions including cell proliferation, differentiation, and apoptosis. 5 , 20 Recently, several studies have documented the involvement of PACE4 in oncogenic processes in various types of cancers including oral tongue cancer, liver cancer, skin cancer, prostate cancer, lung cancer, and glioma. 6 , 11 - 15 , 18 However, until now, no study has explored the expression of PACE4 and its potential impact in NPC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In addition, PACE4 is involved in the regulation of various cellular processes such as proliferation, differentiation, and apoptosis. 5 8 Previous studies showed that PACE4 was clearly down-regulated in ovarian cancer cell lines, such as Hey and Hey-C cells, and a series of primary ovarian tumors. 9 , 10 Nevertheless, accumulating studies have highlighted PACE4 for its potential role in certain human malignancies such as oral tongue carcinoma, 11 hepatocellular carcinoma, 12 glioma, 13 skin cancer, 6 , 14 prostate cancer, 15 and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These results as well as the previous report indicate that low expression levels of the genes related to interferons may be the major determinants of the poor in vitro development of OGCs. PCSK6, a member of the proprotein convertase family, is involved in inhibition of apoptosis of granulosa cells in preovulatory human follicles [30], and PCSK6 -mutant mice show a loss of ovarian function [31]; these data are suggestive of low expression of the genes associated with impaired development of OGCs.…”
Section: Discussionmentioning
confidence: 99%